2008
DOI: 10.1007/s10661-008-0621-y
|View full text |Cite
|
Sign up to set email alerts
|

Butyltin levels in several Portuguese coastal areas

Abstract: This work aimed to report present levels (2007-2008 sampling) of tri- (TBT), di- (DBT), and monobutyltin (MBT) in surface sediments from 11 Portuguese coastal sites and discuss the evolution of BTs contamination in the last two decades. All the samples revealed quantifiable values of TBT, DBT, and MBT with total butyltin concentrations between 1 and 565 ng/g (of Sn in dry sediment). Maximum level of TBT, 66 ng/g, was observed in Sado estuary, at Lisnave site, in the proximity of a big shipyard. MBT decreased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
(24 reference statements)
0
4
1
Order By: Relevance
“…Sediment TBT concentrations near a shipyard in Otuschi Bay (14,000 ng Sn/g) in Japan and Chennai port (11,871 ng Sn/g) in India were a little lower than our values in this study but in the same order of magnitude [9,12]. Except for some studies reporting tens (or hundreds) of ppb of TBT levels (Sado Estuary, Kaohsiung Harbor, and Gohyeon Bay) [22][23][24], the other regions in Table 2 showed TBT concentrations in the range of from 1137 to 5372 ng Sn/L [8,[24][25][26]. TBT concentrations in surface sediments from Gohyeon Bay in this study are higher than levels reported in other shipyard areas in Ulsan Bay (13,300 ng Sn/g) and Okpo Bay (11,700 ng Sn/g), South Korea in 1996, 7 years before the total ban of TBT [14].…”
Section: Comparison Of Butyltin Contamination With Other Studiescontrasting
confidence: 68%
“…Sediment TBT concentrations near a shipyard in Otuschi Bay (14,000 ng Sn/g) in Japan and Chennai port (11,871 ng Sn/g) in India were a little lower than our values in this study but in the same order of magnitude [9,12]. Except for some studies reporting tens (or hundreds) of ppb of TBT levels (Sado Estuary, Kaohsiung Harbor, and Gohyeon Bay) [22][23][24], the other regions in Table 2 showed TBT concentrations in the range of from 1137 to 5372 ng Sn/L [8,[24][25][26]. TBT concentrations in surface sediments from Gohyeon Bay in this study are higher than levels reported in other shipyard areas in Ulsan Bay (13,300 ng Sn/g) and Okpo Bay (11,700 ng Sn/g), South Korea in 1996, 7 years before the total ban of TBT [14].…”
Section: Comparison Of Butyltin Contamination With Other Studiescontrasting
confidence: 68%
“…The ability of sediments to accumulate the compounds varies geographically and geologically. The geological element is based on the physicochemical characteristics of sediment such as particle size and organic carbon content [42,43]. Generally, the concentrations of BTs in the sediments collected from this seagrass area are lower than those reported at other locations, such the studies conducted in the semi-closed Port of Gdynia [44], fishing ports along the Chinese coast [45], Southern Baltic coastal zone [46], Kaohsiung Harbour, Taiwan [47], and Korean Special Management Sea Areas [48].…”
Section: Concentration Of Organotin Compounds In Sedimentsmentioning
confidence: 98%
“…In concurrence with the European Directive 79/117/CEE, nine OCP were banned by decree, including DDT, the 'drins' (aldrin, dieldrin and endrin), heptachlor, and HCH (Ordinance 660/88). However, these substances are still detected decades later in the physical environment (Cardoso et al 2009;Carvalho et al 2009), in food products S. Espín 1985-2022 ( Correia-Sá et al 2012) and in humans (Lino and da Silveira 2006;Lopes et al 2014).…”
mentioning
confidence: 99%